Characterization of human islet function in a convection‐driven intravascular bioartificial pancreas. Issue 2 (14th December 2022) - Santandreu, Ana G.; Taheri‐Tehrani, Parsa; Feinberg, Benjamin; Torres, Alonso; Blaha, Charles; Shaheen, Rebecca; Moyer, Jarrett; Wright, Nathan; Szot, Gregory L.; Fissell, William H.; Vartanian, Shant; Posselt, Andrew; et al.
Abstract: Clinical islet transplantation for treatment of type 1 diabetes (T1D) is limited by the shortage of pancreas donors and need for lifelong immunosuppressive therapy. A convection‐driven intravascular bioartificial pancreas (iBAP) based on highly permeable, yet immunologically protective, silicon nanopore membranes (SNM) holds promise to sustain islet function without the need for immunosuppressants. Here, we investigate short‐term functionality of encapsulated human islets in an iBAP prototype. Using the finite element method (FEM), we calculated predicted oxygen profiles within islet scaffolds at normalized perifusion rates of 14–200 nl/min/IEQ. The modeling showed the need for minimum in vitro and in vivo islet perifusion rates of 28 and 100 nl/min/IEQ, respectively to support metabolic insulin production requirements in the iBAP. In vitro glucose‐stimulated insulin secretion (GSIS) profiles revealed a first‐phase response time of <15 min and comparable insulin production rates to standard perifusion systems ( 10 pg/min/IEQ) for perifusion rates of 100–200 nl/min/IEQ. An intravenous glucose tolerance test (IVGTT), performed at a perifusion rate of 100–170 nl/min/IEQ in a non‐diabetic pig, demonstrated a clinically relevant C‐peptide production rate (1.0–2.8 pg/min/IEQ) with a response time of <5 min.